Advanced Visual Interfaces. Supporting Big Data Applications AVI 2016 Workshop, AVI-BDA 2016, Bari, Italy, June 7-10, 2016, Revised Selected Papers - Bornschlegl, Marco X.; Engel, Felix C.; Bond, Raymond; Hemmje, Matthias L. (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the thoroughly refereed post-workshop proceedings of the AVI 2016 Workshop on Road Mapping Infrastructures for Advanced Visual Interfaces Supporting Big Data Applications in Virtual Research Environments, AVI-BDA 2016, held in Bari, Italy, in June 2016. The 10 revised full papers in this volume present the elaborated outcome of the initial position papers capturing the results oft the roadmapping discussions in the workshop at which comments of several external reviewers for these full publications were also integrated.